Are dietary interventions effective at increasing fruit and vegetable consumption among overweight children? A systematic review. Issue 5 (16th January 2014) - Bourke, Michael; Whittaker, Paula J; Verma, Arpana
Abstract : Introduction: Childhood obesity is now a global epidemic and the incidence continues to increase. Dietary interventions and nutritional education are possible options to manage childhood obesity. However, restrictive diets can result in negative outcomes, and therefore it may be more apt to encourage children to consume more fruit and vegetables and thereby develop a healthier positive attitude towards food. Method: A systematic review of literature of interventions to increase fruit and/or vegetable consumption in overweight or obese children and adolescents was conducted, applying a free-text strategy with a set of search terms. Results: A total of five studies describing seven interventions published in international peer-reviewed journals and meeting the review's eligibility criteria were identified. All five studies examined family-focused interventions to increase daily fruit and vegetable consumption measured either by child self-report or parent report. Only one intervention reported a lasting statistically significant increased consumption of fruit and vegetables. Conclusions: This review highlights that in order to tackle obesity narrow interventions focusing on single aspects of behaviour are unlikely to achieve long-term change. Successful public health interventions tackling childhood obesity will need to take a holistic approach and target behaviour change in multiple aspects of children's lifestyles and their surroundings, including nutritional education, parental support and physical activity.